Study of the Role of Family Education in Islam: Empirical Study at Malang International Islamic Boarding School - Kusnadi, Kusnadi; Mutniati, Vebri Putri; Ulfaturrahmah, Ulfaturrahmah; Latif, Muhammad Sabri; Muafaq, M. Fadil (Jurnal Mediasas: Media Ilmu Syari’ah dan Ahwal Al-Syakhsiyyah, 2023)
In the current era of globalization, many schools are competing to improve their quality, the output that is paid attention to is not only improving the cognitive domain but also the character of students. Unfortunately, there are still many levels of crime that occur in schools such as bullying and the loss of Islamic values ??and manners. school. Of course, overcoming this problem is not only the school’s responsibility. However, the role of the family environment as the first tricenter of education before school certainly plays an important role in instilling education. The family is the first environment that God presents to a child to start his life. This research aims to explore how to build family education at the International Islamic Boarding School in Malang City, and the challenges in family education at the International Islamic Boarding School in Malang City. The method in this research uses a qualitative approach with a case study method. Data collection techniques include participatory observation, in-depth interviews and documentation studies which are analyzed using the Miles and Huberman model through data processing, data presentation and verification or drawing conclusions. The research results show that building family education at the International Islamic Boarding School (IIBS) Malang City starts before marriage by choosing a good partner and understanding the importance of knowledge about marriage, family and parenting. As well as providing practical recommendations about the role of family education in Islam.